Sister's Inn (partial exterior) (1950)
Photograph taken outside of Sister's Inn (name partially in photo) featuring two men and one woman next to a 1955 Chevy four door sedan. Handwriting on back claims Sister's Inn to be the first black restaurant in SLO.